2017
DOI: 10.1002/ppap.201700087
|View full text |Cite
|
Sign up to set email alerts
|

Magnetical asymmetric effect in geometrically and electrically symmetric capacitively coupled plasma

Abstract: Magnetical asymmetric effect (MAE) in a geometrically and electrically symmetric capacitively coupled plasma is investigated by a one‐dimensional implicit Particle‐in‐cell/Monte Carlo collision simulation. We applied four types of asymmetric magnetic field parallel to the electrodes and the discharge operates at a single‐frequency rf source of 13.56 MHz and 150 V in argon with the pressure of 30 mTorr. The simulation results show that the asymmetric magnetic field can generate a significant dc self‐bias, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…Moreover, the ion flux can be adjusted in this way [20]. Oberberg et al [21] also found that tuning such axially non-uniform magnetic fields in low pressure CCPs allows to control the self-excitation of the plasma series resonance (PSR) and Non-Linear Electron Resonance Heating (NERH) in space and time due to the magnetic control of the plasma symmetry [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ion flux can be adjusted in this way [20]. Oberberg et al [21] also found that tuning such axially non-uniform magnetic fields in low pressure CCPs allows to control the self-excitation of the plasma series resonance (PSR) and Non-Linear Electron Resonance Heating (NERH) in space and time due to the magnetic control of the plasma symmetry [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 34 35,36 have used an asymmetric magnetic field with variable gradients to create asymmetry in the configuration of a CCP device. Their particle simulation studies show that the magnetic field asymmetry provides a means of independently controlling the ion flux and ion energy.…”
mentioning
confidence: 99%
“…Other recent studies devoted to CCP operation in the presence of an external magnetic field 26,27,34 , have explored somewhat different effects. S. Yang et al 35,36 have used an asymmetric magnetic field with variable gradients to create asymmetry in the configuration of a CCP device. Their particle simulation studies show that the magnetic field asymmetry provides a means of independently controlling the ion flux and ion energy.…”
mentioning
confidence: 99%
“…The method has frequently been applied in studies of dual-frequency RF discharges [62,63], plasma sources operated under the conditions where electrical asymmetry develops [64,65], as well as in investigations of discharges driven by Tailored Voltage Waveforms [66][67][68][69]. Related to this, the effects of various asymmetries, like those created by a magnetic field [70], by unequal secondary electron yields at the two electrodes [71,72] have been investigated, as well as the interplay between geometrical and electrical asymmetry effects in CCPs [6,73]. A similarity law and the frequency scaling properties of CCPs were recently reported [74].…”
Section: Introductionmentioning
confidence: 99%